Prosthetic Rehabilitation of Velopharyngeal Insufficiency: Pharyngeal Obturator Prostheses with Different Retention Mechanisms - Tuna, Suleyman Hakan; Pekkan, Gurel; Gumus, Hasan Onder; Aktas, Alper (European Journal of Dentistry, 2010)
Pharyngeal obturator prostheses restore the congenital or acquired defects of the soft palate and allow adequate closure of palatopharyngeal sphincter. Two patients with soft palate defect and subsequent velopharyngeal insufficiency were rehabilitated using pharyngeal obturator prostheses which had different retention mechanisms. Since it is necessary for swallowing and intelligible speech, the patients were examined in terms of adequate velopharyngeal closure after prosthetic treatment. The results were satisfying for both the patients and physicians. (Eur J Dent 2010;4:81-87)
Keywords: Pharyngeal obturator; Velopharyngeal insufficiency; Hypernasality; Retention